2012
DOI: 10.1007/s00737-012-0285-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brief psychoanalytic intervention for perinatal depression

Abstract: This pilot study explores the effects of a brief individual psychoanalytic therapy on perinatal depressive symptoms. This intervention is based on the Geneva's mother-infant intervention model. A sample of 129 pregnant women was recruited in Geneva (Switzerland) and screened for depressive symptoms with two instruments: the 'Edinburgh postnatal depression scale' (EPDS) and the 'Dépistage anténatal de la dépression postnatale'. A group of 40 women presenting depressive symptoms (treatment group) participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…In a recent study of mothers with PND, Nanzer et al (2012) found that short-term parent–child treatments with a psychodynamic approach seem to be particularly appropriate for the perinatal period because they are focused on parenthood and on the difficulties faced in relation to the identity change that becoming a parent brings. The authors found that by discussing and modifying distorted maternal representations, treatment can reduce the mother’s sense of guilt and depression and anxiety symptoms related to it.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of mothers with PND, Nanzer et al (2012) found that short-term parent–child treatments with a psychodynamic approach seem to be particularly appropriate for the perinatal period because they are focused on parenthood and on the difficulties faced in relation to the identity change that becoming a parent brings. The authors found that by discussing and modifying distorted maternal representations, treatment can reduce the mother’s sense of guilt and depression and anxiety symptoms related to it.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported on rates of agreement to participate in intervention trials among women already screened for perinatal depression [16,17], but few have recorded rates of agreement to screening procedures themselves among women attending obstetrics clinics who are approached to participate in research [18–20]. Consequently, the findings of research studies that target pregnant women who are experiencing depression (particularly untreated major depressive disorder) are often limited by small or homogeneous sample populations [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the potential risks related to prenatal maternal emotional distress, the findings of the study add to literature highlighting the relevance of early detection and intervention. Regarding this, a recent study (Clatworthy, 2012) has supported the effectiveness of intervention starting in the prenatal period to prevent postnatal depression in high-risk women, while other authors have successfully tested the efficiency of a brief perinatal intervention centred on parenthood to foster the parent-infant relationship (Nanzer et al, 2012).…”
Section: Activitymentioning
confidence: 97%